Pemanfaatan Aplikasi Krealogi Guna Optimalisasi Proses Bisnis UMKM Al-Farizi Tapis Lampung - Pratisti, Cahyani; Wahyuningsih, Yusminar; Riyana, Evi Desi (IAI Darussalam, 2024)
MSMEs AL Farizi Tapis is one out of the MSMEs within the province of Lampung whose method of listing orders, stock, and bookkeeping is done physically and never makes even a business report. The problem is that MSME’s decline order. The problem that occurs is that MSMEs refuse orders because there are no raw materials or the time to purchase raw materials takes a long time, as well as the processing time which is felt to be tight so there is concern that the filter craft will not be on time. Apart from that, bookkeeping which is done manually is also difficult because it often happens that people forget to record or there are missing notes regarding orders and transactions. MSMEs have never carried out warehouse management so they don't know what stock of raw materials is still available or has run out. A simple integrated application is needed that can help MSMEs organize production schedules, order recording, transaction records, warehouse management, and financial reports to optimize MSME business processes. The service used Participatory Action research and training methods. After carrying out service, MSMEs can use the Krealogi application so they can minimize incorrect recording or loss of order records or sales transactions, missed production plans, and the absence of financial reports.